2017
DOI: 10.1007/s11538-017-0286-1
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Oscillation Frequency-Sensitive Gene Regulation and Homeostatic Compensation in Pancreatic $$\upbeta $$-Cells

Abstract: Pancreatic islet [Formula: see text]-cells are electrically excitable cells that secrete insulin in an oscillatory fashion when the blood glucose concentration is at a stimulatory level. Insulin oscillations are the result of cytosolic [Formula: see text] oscillations that accompany bursting electrical activity of [Formula: see text]-cells and are physiologically important. ATP-sensitive [Formula: see text] channels (K(ATP) channels) play the key role in setting the overall activity of the cell and in driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Lightman and colleagues (Spiga et al., ) have developed mathematical models to explore the interaction between the circadian clock and this ultradian endocrine rhythm. Furthermore, a mathematical modelling study of pancreatic islet β‐cells has shown that calcium‐dependent transcription can adjust potassium channel activity to rescue electrical bursting and insulin oscillations (Yildirim & Bertram, ). Circadian rhythms also modulate cortical excitability and EEG synchrony (Ly et al., ).…”
Section: Modelling Section 4: Future Directions For Mathematical Modementioning
confidence: 99%
“…Lightman and colleagues (Spiga et al., ) have developed mathematical models to explore the interaction between the circadian clock and this ultradian endocrine rhythm. Furthermore, a mathematical modelling study of pancreatic islet β‐cells has shown that calcium‐dependent transcription can adjust potassium channel activity to rescue electrical bursting and insulin oscillations (Yildirim & Bertram, ). Circadian rhythms also modulate cortical excitability and EEG synchrony (Ly et al., ).…”
Section: Modelling Section 4: Future Directions For Mathematical Modementioning
confidence: 99%
“…These features include spike frequency during the burst, dynamics during the silent phase (oscillatory or not), shape of the burst (on a plateau compared to the silent phase or, on the contrary, with undershoots). These 3 features led Rinzel to name 3 classes: square-wave bursting , observed in a number of recordings and models of pancreatic beta-cells [ 47 ] among other [ 48 ]; elliptic bursting , observed in various neural recordings and models of sensory neurons [ 15 , 49 ]; and parabolic bursting , initially observed in the Aplysia R15 neuron [ 42 ] and ever since in various neural models [ 50 ]. We show an example of each class in Fig 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Bursting oscillations play an integral role in insulin secretion by pancreatic -cells 84 , and these cells can compensate for genetic deletions of a critical channel K(ATP) channel population by over-expressing other potassium channels 86 in the mouse, but not in humans. Recent work suggests that these cells can use intracellular calcium as a sensor of voltage dynamics in a negative feedback loop to regulate activity 87 . Thus, many other cell types may share common features of homeostatic regulation with neurons such as robustness to size changes and sensitivity to some perturbations 88 .…”
Section: Discussionmentioning
confidence: 99%